Comparison of the Hemagglutination Inhibition Test and IgG ELISA in Categorizing Primary and Secondary Dengue Infections Based on the Plaque Reduction Neutralization Test. (30th June 2016) - Lukman, Nurhayati; Salim, Gustiani; Kosasih, Herman; Susanto, Nugroho Harry; Parwati, Ida; Fitri, Silvita; Alisjahbana, Bachti; Widjaja, Susana; Williams, Maya
Abstract : Secondary dengue infection by heterotypic serotypes is associated with severe manifestations of disease, that is, dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). The World Health Organization (WHO) has recommended criteria based on the hemagglutination inhibition (HI) test to distinguish between primary and secondary dengue infections. Since the HI test has practical limitations and disadvantages, we evaluated the accuracy of WHO HI criteria and compared it with criteria based on an IgG enzyme-linked immunosorbent assay (ELISA) using a plaque reduction neutralization test (PRNT) as the gold standard. Both WHO HI criteria and IgG ELISA criteria performed strongly (16/16) in determining primary infection. However, to determine secondary infection, the IgG ELISA criteria performed better (72/73) compared to the WHO HI criteria (23/73).